Characteristics of Orange-Footed Scrubfowl (Megapodius reinwardt) Nest in Tunak Montain Natural Tourism Park - Hasbudiana, Anisa; Yamin, M.; Jamaluddin, Jamaluddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Orange-footed scrubfowl (Megapodius reinwardt) is a protected animal. Especially on the island of Lombok, one of the habitats of the orange-footed scrubfowl bird is in Tunak Montain Nature Tourism Park. The condition of the nest will influence the frequency of presence of orange-footed scrubfowl. In this regard, to enrich information in its conservation, it is necessary to carry out research on the characteristics of the nests of the orange-footed scrubfowl. The aim of this research to determine the nest characteristics of the orange-footed scrubfowl in Tunak Montain Nature Tourism Park. The method used is direct measurement and observation in the field. The results of the research show that the nest of the orange-footed scrubfowl bird is in the form of a mound of earth composed of leaves, branches, tree twigs, sand and rocks. The height of the nest mound ranges from 57-160 cm, and the diameter of the nest mound is 500-1,030 cm. The number of holes in each nest varies, namely between 5-9 holes, with a hole depth of 67-142 cm and a nest hole diameter of 30-41 cm. The dominant factors of the abiotic component of the nest that have a singular influence on the presence of orange-footed scrubfowl are distance to the river channel and number of predators. The tendency to choose a nesting area based on the results of Chi-Square analysis is influenced by five variables, namely, distance to the river, soil texture, altitude, temperature and number of predators around the nest.